THE CORRELATION BETWEEN READING ENGLISH NOVEL HABIT AND VOCABULARY MASTERY IN ENGLISH EDUCATION DEPARTMENT STUDENTS’ BATCH 2014 OF UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Dian Rahmawati Hardi (PBI 15 UMY 070, 2015)
*70 Reading has an important role because it appears in each language skills and one of the aspects of the most dominant to increase the vocabulary mastery. It is supported by Brown (2001), which explains that the more vocabulary students have, students will easily understand the reading and vice versa. This study aims to: describe the level of the reading English novels habit; describe the vocabulary mastery; and the relationship between reading English novels habit and vocabulary mastery. The population in this study of English Education Department batch 2014 Universitas Muhammadiyah Yogyakarta, was 156 students. The sample of research was 45 students. The data collection used two tests. They were questionnaires and multiple-choice tests. This research used the validity and reliability test. The analysis technique used was a product moment correlation. All the data gained in this research concluded: (1) The level of the reading English novels habit mostly fall into the category sometimes amounted to 33.3% and category often 33.3%. (2) Analysis descriptive vocabulary mastery concluded that most of the English Education Department students batch 2014 at Universitas Muhammadiyah Yogyakarta in the category was very good it is 46.7%. (3) There is a positive and significant relationship between the reading English novels habit and vocabulary mastery with a correlation value of 0.424 and 0.004 was significance. The data result of the research shows that the students reading English novel habit of English Education Department batch 2014 UMY is medium and the students vocabulary mastery is good. The Reading English novel habit and vocabulary mastery shows that there is a correlation between each variable. Therefore, it concludes to increase the students vocabulary mastery. This is because in the English novel there is a lot of new vocabulary that can improve the vocabulary mastery.